Comparative of Outpatient Queue Services for Government Hospitals and Islamic Hospitals in Medan - Rapotan Hasibuan (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Differences in service characteristics between government and Islamic hospitals highlight the importance of translating the Islamic sharia system into measurable and objective health service quality. This study, therefore, aimed to determine the comparison of queuing time, perception and patient satisfaction related to the queue of outpatient services at the hospital. Analytical survey approach with cross sectional research design through observation of queue duration with the help of a stopwatch and questionnaire sheets related to patient perception. The study was conducted at the Dr. Pirngadi Government Hospital (PGH) and Malahayati Islamic Hospital (MIH) in Medan, involving as many as 300 patients. The mean difference test was used with the Jeffreys's Amazing Statistics Program (JASP) application 0.9.1 version. This study found that there were significant differences in poly queue time (p=0.000), outpatient waiting time (p=0.043), pharmacy queue time (p=0.001), and total time (p=0.002) between the two hospitals. The findings of this research indicate substantial variances in poly queue time, outpatient waiting time, pharmacy queue time, and total time between the two hospitals, although no significant disparities were observed in terms of satisfaction. Keyword: Government hospital, Health service, Islamic hospital, Satisfaction, Queue